Thickness determination of the tidemark of human articular cartilage using high-resolution micro-XRF imaging of zinc and lead. Issue 3 (September 2021) - Rauwolf, M.; Turyanskaya, A.; Wobrauschek, P.; Sawhney, K.; Roschger, A.; Roschger, P.; Streli, C.; Hofstaetter, J.G.
Abstract: Objective: The objective of the study was to specify the thickness of Zn and Pb accumulation within the tidemark (TM), a narrow structure between the non-calcified and the calcified articular cartilage. It is considered an active or resting calcification front. This banded structure of the cartilage-bone interface is known to undergo changes in osteoarthritis. Therefore, gaining knowledge about this structure is of interest. Methods: Femoral head samples were collected from patients suffering from various bone diseases, 6 samples have been investigated. Thin bone slices (3 ​μm thick) were measured with high resolution synchrotron micro-X-ray fluorescence (SR micro-XRF) analysis using a beam with dimensions of 500 ​× ​800 ​nm 2 . The tidemark region was found in all analyzed samples. The Savitzky-Golay filter was used to smooth the measured imaging data and Kaplan-Meier estimation to gain reliable tidemarks medians for Pb and Zn. To our knowledge this was the first time that these methods have been applied to gain information on histological structures obtained by elemental imaging. Results: The thickness of the Zn and Pb layer ranged from about 3 to 11 ​μm for Zn and 4–14.5 ​μm for Pb. Our Zn ratios (TM/matrix) were found to be 1.5-3-fold ratio between Zn tidemark values and in mineralized matrix and are similar in all samples. Conclusions: The determined thickness of the layer is much smaller than found in previous measurements with the beam having 20 ​× ​14 ​μm 2 size. The Zn ratios agree with our previous findings.